Visiones sobre el alcohol y la prohibición en los debates médicos y la prensa en Colombia, 1918-1923 (2017)
ABSTRACT: Between 1918 and 1923, the influence of alcoholism in the degeneration of the “Colombian races” was frequently discussed. It was a debate marked by regionalist points of view. Using the terminology of degeneration theory, Antioquia’s Departmental Assembly proposed a Dry Law similar to USA’s prohibition law, which led to the adoption of Law 88 of 1923 or “Anti-alcoholic Law”. This paper analyzes the medical writings on alcoholism and degeneration, as well as articles published in two of Antioquia’s newspapers regarding the Prohibition, intending to reconstruct the raised tension among morality, medicine and politics during the approval process of Law 88.